From Picture to Movie: Twenty Years of Ground Deformation Recording Over Tuscany Region (Italy) With Satellite InSAR - Bianchini, Silvia; Raspini, Federico; Solari, Lorenzo; Del Soldato, Matteo; Ciampalini, Andrea; Rosi, Ascanio; Casagli, Nicola (Frontiers in Earth Science, 2018)
Synthetic Aperture Radar Interferometry (InSAR) techniques have been long exploited for detecting and mapping slow-moving ground surface displacements due to their millimetre accuracy, non-invasiveness and wide area coverage. A review on different applications of Persistent Scatterers InSAR approaches, proposed and applied over Tuscany region (Italy) across time, is here presented. The study area is characterized by both subsidence of alluvial plains and landslides on hilly and mountainous reliefs. Tuscany has a leading role in Italy in the field of interferometric applications: the first InSAR analysis, which date back to 2003, have been performed at local basin scale, by exploiting various PSI-based approaches for risk mapping. First InSAR applications at regional scale date back to 2009, relying on historical SAR archives of ERS and ENVISAT satellites for updating subsidence and landslide inventory maps at a certain temporal date. Nowadays, the availability of Sentinel-1 SAR data with a regular and systematic 6-days acquisitions plan, allows a near-real time monitoring of deformative scenario at regional scale rather than a solely mapping of geo-hydrological phenomena. Last innovative InSAR applications over Tuscany region scan the territory, exploiting the regular repeat pass of Sentinel-1, and promptly highlight the sites affected by the highest ground movements with high temporal frequency. Such approach permits to pass from a static ‘picture’ of the regional slope instability up to a weekly-updated ‘movie’ with improved detail, useful for civil protection practices. These last ongoing works significantly enhance the value of multi-temporal InSAR approaches for investigating and managing geo-hazards over the Region.